Current oral hygiene and recreational behavioral trends in HIV disease - Mercante, Donald E.; Guarisco, Emily; Lilly, Elizabeth A.; Rao, Arni; Treas, Kelly; Beall, Clifford J.; Thompson, Zach; Griffen, Ann L.; Leys, Eugene J.; Vazquez, Jose A.; Hagensee, Michael E.; Fidel, Paul L. (Clinical and experimental dental research, 2023)
Objective HIV disease is evolving with more HIV+ persons experiencing a high quality of life with well‐controlled viremia. We recently enrolled a large cohort of HIV+ and clinically relevant HIV− persons for oral microbiome analyses that included a questionnaire related to oral hygiene and recreational behaviors. Here, the questionnaire responses were analyzed for behavioral trends within the cohort, together with trends over time by comparison to a previous geographically centered HIV+ cohort. Methods Data were collected by questionnaire at baseline visits as cross‐sectional assessments. Multivariable analyses were conducted for associations of HIV status as well as age, race, and sex, on oral hygiene/recreational behaviors. Results HIV+ subjects had reduced brushing frequency, but increased incidence of past cleanings and frequency of dry mouth, compared to the HIV− subjects. Within the entire cohort, positive associations were identified between age and several oral hygiene practices, and between age, race, and sex for several recreational behaviors. In comparison to the historical cohort, the contemporary HIV+ cohort participated in fewer high‐risk behaviors, but with similar trends for smoking and oral hygiene practices. Conclusion HIV status had little association with oral hygiene and recreational behaviors despite several differences in age, race, and sex. Behavioral trends over time support a higher quality of life in people currently living with HIV.